(Just) Give Me A Reason … - Laffranque, Julia (Juridica International, 2018)
Judicial systems often wrestle with whether to sacrifice always presenting thorough judicial reasoning for the sake of an effective leave-to-appeal system. The paper outlines issues of reference to the Luxembourg Court, particularly with regard to Estonian circumstances in light of the ECtHR judgment in Baydar v. the Netherlands. The interplay between EU law and the European Convention on Human Rights in this regard is considered first, along with the importance of giving reasons, courts’ authority, the different roles of domestic and European courts, the duty of referring questions to the CJEU and exemption, consequences of non-referral in EU law, the Strasbourg Court’s role in dialogue between national courts and the CJEU, etc. Examined next are such matters as influences on preliminary references in European Union law, summary reasoning and limits to the reasoning duty (especially with regard to the Ullens de Schooten case of the ECtHR), associated division of competencies between the Strasbourg and Luxembourg courts, and finally the reasoning of the ECtHR itself as good or bad example. The author then considers the Supreme Court of Estonia’s leave-to-appeal system and the national courts’ practice in relation to Baydar, concluding that, while reasoned judgments are important and a right, no right exists for the applicant’s case to be referred by a domestic judge to the Luxembourg Court, though it is vital that summary judgment not be arbitrary / manifestly unreasonable; that Estonian courts have made reasonable use of the preliminary reference procedure before the Luxembourg Court thus far; and that they should articulate well the reasoning for referral/non-referral for litigants. The author proposes that the Estonian Supreme Court explain, exceptionally in one refusal of leave to appeal (cf. the Netherlands), that the general requirements for granting leave to appeal cover also the situation of preliminary questions to the CJEU and C.I.L.F.I.T. arguments of the CJEU. Above all, neither the interplay between EU law and the European Convention on Human Rights nor the role of national courts finding their way in complex legal surroundings should be neglected.